Proteomics for the Investigation of Surface-Exposed Proteins in Probiotics - Siciliano, Rosa Anna; Lippolis, Rosa; Mazzeo, Maria Fiorella (Frontiers in Nutrition, 2019)
Probiotics are commensal microorganisms that are present in the intestinal tract and in many fermented foods and positively affect human health, promoting digestion and uptake of dietary nutrients, strengthening intestinal barrier function, modulating immune response and enhancing antagonism towards pathogens. The proteosurfaceome, i.e. the complex set of proteins present on the bacterial surface, is directly involved as leading actor in the dynamic communication between bacteria and host. In the last decade, the biological relevance of surface-exposed proteins prompted research activities exploiting the potentiality of proteomics to define the complex network of proteins that are involved in the molecular mechanisms at the basis of the adaptation to gastrointestinal environment and the probiotic effects. These studies also took advantages of the recent technological improvements in proteomics, mass spectrometry and bioinformatics that triggered the development of ad hoc designed innovative strategies to characterize the bacterial proteosurfaceome. This mini-review is aimed at describing the key role of proteomics in depicting the cell wall protein architecture and the involvement of surface-exposed proteins in the intimate and dynamic molecular dialogue between probiotics and intestinal epithelial and immune cells.